Seremban transport interchange / Azmi Abdul Rahim - Abdul Rahim, Azmi (Faculty of Architecture, Planning and Surveying, 1984)
This report is prepared as part of the Final Design Thesis which is the requirement towards completing the Advanced Diploma in Architecture of Mara Institute of Technology. As per requirements, the subject of the Design Project is live and real. Findings have been based on actual research and through consultancy with professional consultants and advising lecturers. The Final Research Design Thesis attempts as much as / possible to cover all aspects of planning and design as well as management that may be present in the actual project.